Preparation and application method of inorganic polymer repairing material
By preparing the repair materials of the wireless polymer, the use of waste materials such as ceramic waste residue and shell fine aggregate solve the problem of environmental pollution caused by excessive use of concrete in the repair of old buildings, and realize the efficient utilization and cost of resources.
Patent Information
- Application Number
- CN202411455518.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-28
AI Technical Summary
When repairing old buildings, the existing technology requires a large amount of concrete, which leads to high consumption of environmental resources and cement production will produce a large amount of carbon dioxide, which seriously pollutes the natural environment.
The preparation method of inorganic polymer repair materials is used to mix ceramic waste residue powder, shell fine aggregate, shell powder and alpine molten powder, and add alkaline stimulus solution and aluminum fiber to form inorganic polymer repair materials. This material not only reduces the use of reinforced concrete, but also uses waste materials to reduce the cost of use of raw materials.
In the case of not affecting the performance of the material, the recycling and use of waste materials for the repair of old buildings, reducing the use of concrete, reducing environmental pollution and resource consumption, and reducing the cost of material.
Smart Images

Figure BDA0005090344860000061 
Figure HDA0005090344870000011 
Figure HDA0005090344870000012
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of repairing steel bar corrosion in old buildings, and in particular to a preparation and application method of an inorganic polymer repair material. Background Art
[0002] In recent years, the construction of urban appearance in my country has been basically completed, and there are fewer and fewer new buildings in the city center. The problem involved in more construction in the future is the repair of old houses and other buildings. In addition, the existing buildings use reinforced concrete structures mixed with excessive chloride salts due to the requirements of early strength or frost protection. There are many cases of concrete cracking, peeling, and component damage caused by steel corrosion. In addition, due to improper application of concrete admixtures or construction and raw material quality, corrosion of reinforced concrete continues to occur. In addition, the erosion of acid rain has caused damage to the building structure and reduced the bearing capacity of the building. This is a huge challenge for the future use of the building. Therefore, repairing and maintaining the building is an important direction in the future.
[0003] However, traditional repair methods require a large amount of concrete, which contains about 12% cement, 8% water and 80% sand and gravel. According to this ratio, the world's annual demand for concrete is about 11.5 billion tons, which means 1.5 billion tons of cement, 1 billion tons of water and 9 billion tons of sand and gravel. The water and sand and gravel required to produce concrete will cause a great consumption of environmental resources. The production of 1.5 billion tons of cement will produce about 1.5 billion tons of carbon dioxide, accounting for about 5% of the global carbon dioxide production, which is a major cause of the greenhouse effect. In addition, my country's cement production accounts for 37% of the world's production, and the carbon dioxide emissions generated by the cement industry account for 6%-8% of the national emissions, which seriously pollutes the natural environment. Therefore, reducing the use of concrete has a positive effect on protecting natural resources and reducing the greenhouse effect.
[0004] Based on the above, the present invention proposes a preparation and application method of a green and environmentally friendly inorganic polymer repair material, which can not only recycle waste materials for repairing old buildings without affecting the material performance, but also reduce the use of reinforced concrete. Summary of the invention
[0005] The present invention aims at solving the problems in the prior art and provides a method for preparing and applying an inorganic polymer repair material.
[0006] To achieve the above object, the present invention adopts the following technical solutions:
[0007] (I) The present invention provides a method for preparing an inorganic polymer repair material, comprising: mixing and stirring ceramic waste slag powder, shell fine aggregate, shell powder and kaolin powder, then adding an alkali activator solution to the completely stirred dry material, and continuing to stir so that the dry material and the alkali activator are fully in contact and react; adding alumina fibers to the stirred mortar slurry at a uniform speed in batches, and continuing to stir after all the alumina fibers are added to obtain an inorganic polymer repair material.
[0008] Furthermore, the mixing mass ratio of the ceramic waste powder, shell fine aggregate, shell powder and kaolin powder, alkali activator and alumina fiber is (180-450):900:(180-450):(180-360):393.2:19.4.
[0009] Furthermore, the preparation method of the ceramic waste powder is: washing the ceramic waste and drying it to constant weight, sieving it after cooling it to room temperature, and ball-milling the sieved ceramic waste to obtain ceramic waste powder, wherein the particle size of the ceramic waste powder is not greater than 10 μm.
[0010] Furthermore, the preparation method of the shell fine aggregate is: washing the discarded shells with acetic acid to remove the organic matter remaining on the surface, then washing, drying and crushing, sieving and removing impurities after crushing to obtain particles with a size of 100-180 mesh, 80-120 mesh and 40-80 mesh; the mass ratio of the three is 3:5:2; the shell powder is obtained by ball milling and sieving the crushed discarded shells, and the particle size of the shell powder is not more than 0.6mm.
[0011] Furthermore, the preparation method of the alkaline activator is as follows: calcining shell powder with a particle size of no more than 0.6 mm at high temperature, cooling to room temperature, and obtaining calcium oxide powder after ball milling; filtering and removing impurities from lithium battery ternary precursor wastewater, adding sodium carbonate solution and centrifuging to remove precipitates, adjusting the pH to 8-9, evaporating and concentrating the wastewater, crystallizing sodium sulfate and filtering and separating it; mixing sodium sulfate and calcium oxide powder, adding water to dissolve, cooling to room temperature, and obtaining an alkaline activator solution.
[0012] Furthermore, the high-temperature calcination temperature is 950° C., and the calcination time is 2 hours; the mixing mass ratio of the sodium sulfate, calcium oxide powder and water is 330.39:62.81:236.93.
[0013] Furthermore, the preparation method of the metakaolin powder is: metakaolin is prepared by using metakaolin by a calcination heat activation method, specifically: coal-based kaolin is crushed step by step, ground and then pulverized to make the mass fraction of particles larger than 75 μm in the ground coal-based kaolin powder less than 10%, then calcined at high temperature, kept warm and activated for a period of time, quenched and cooled with water, dried and then ground, and passed through a 100-mesh sieve to obtain the desired metakaolin powder.
[0014] Furthermore, the calcination temperature is 800°C and the heat preservation activation time is 2h;
[0015] (ii) The present invention also provides an application method of the inorganic polymer repair material prepared by the preparation method described above, the application method comprising: placing the cold end of a Stirling refrigerator into a part to be repaired, pouring the inorganic polymer repair material into the part to be repaired, and when the poured part begins to harden and the temperature difference between its internal temperature and the surface temperature exceeds a threshold, turning on the Stirling refrigerator to cool the inside of the poured part; when the poured part is completely hardened, removing the Stirling refrigerator, and filling the cavity formed by the removal of the Stirling refrigerator with the repair material, and finally covering the surface with the repair material.
[0016] The beneficial effects of the present invention are:
[0017] (1) Compared with traditional concrete materials, the present invention uses calcium oxide powder obtained by calcining shells and sodium sulfate obtained by recycling the waste liquid of lithium battery ternary precursor as raw materials for alkaline activator, which solves the problem of environmental pollution caused by shell accumulation and the problem of wastewater discharge in the production process of lithium power plants, and reduces the cost of raw materials.
[0018] (2) In the preparation process of the inorganic repair material of the present invention, ground ceramic waste slag and kaolin powder are used as inorganic polymer monomers. Since most factories in my country directly adopt landfill treatment for ceramic waste slag, its cost is close to zero. Coal-based kaolin is cheap as an industrial solid waste. Therefore, it has a price advantage compared with both traditional concrete materials and the commonly used fly ash-kaolin inorganic mineral polymer materials.
[0019] (3) In the present invention, the ground ceramic waste powder is rich in silicon and aluminum components, has fine particles, and contains a large amount of glass phase, which is very suitable for generating CSH gel with ball-milled shell fine aggregate in a mixed alkali activator, which helps to improve the compressive strength.
[0020] (4) The present invention uses waste shells as raw materials to prepare fine aggregates, and uses ceramic waste residues as polymer monomers to fully utilize the two types of waste, thereby turning waste into treasure. It also avoids the problem of traditional landfill methods for treating ceramic waste residues and waste shells occupying a large amount of land and causing serious pollution to the surrounding environment. It has found a new way to reuse ceramic waste residues and shells.
[0021] (5) Alumina fiber is added to the inorganic repair material of the present invention, which has strong tensile strength and strong fire resistance. Therefore, this material can replace reinforced concrete materials. At the same time, because the use of steel bars is reduced, a series of problems caused by steel bar corrosion in the later stage are avoided, and the weight of the material can be reduced. Under high temperature conditions, the original properties will not change. Since most of the repaired buildings are old buildings, there may be a series of problems such as aging lines, and there are fire hazards. Therefore, when the repaired buildings encounter a fire, the material of the present invention can withstand higher temperatures without being damaged.
[0022] (6) The present invention also provides a solution for solving the problem that the hydration heat during the hardening process of the inorganic polymer repair material causes a temperature rise, which leads to a temperature difference between the inside and outside of the repair part and causes cracks. A Stirling refrigerator is added to the repair part to closely monitor the temperature when the repair part hardens and generates heat. When the temperature inside is too high compared to the surface, the cold end of the Stirling refrigerator is used to cool the inside of the repair part, thereby avoiding concrete cracking caused by high temperature. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The initial fluidity test results of the inorganic polymer repair materials prepared in Examples 1 to 6 of the present invention;
[0024] Figure 2 The 3d, 7d and 28d compressive strength test results of the inorganic polymer repair material test blocks prepared in Examples 1 to 6 of the present invention;
[0025] Figure 3 The 3d, 7d and 28d flexural strength test results of the inorganic polymer repair material test blocks prepared in Examples 1 to 6 of the present invention;
[0026] Figure 4 is the ratio of the compressive strength to the flexural strength corresponding to each age of the inorganic polymer repair material test blocks prepared in Examples 1 to 6 of the present invention;
[0027] Figure 5 The test results of the inorganic polymer repair material test block prepared in Example 4 of the present invention under the tensile test. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention and the accompanying drawings. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0029] Example 1
[0030] The present invention provides a method for preparing an inorganic polymer repair material, comprising the following steps:
[0031] Step 1: Preparation of ceramic waste slag powder, shell fine aggregate, shell powder and metakaolin powder:
[0032] 1. Preparation of ceramic waste powder: Wash the ceramic waste and place it in a laboratory oven at 100±5℃ to dry to constant weight. After cooling to room temperature, pass it through a 0.3mm sieve to remove large particles and other impurities. Put the sieved ceramic waste into a planetary ball mill for ball milling (ball milling at 60 rpm for 50-60 minutes) to obtain ceramic waste powder. The particle size of the ceramic waste powder is within 10μm.
[0033] 2. Preparation of shell fine aggregate: The discarded shells are washed with acetic acid at pH=3 to remove the organic matter remaining on the surface, then washed, dried and crushed with a mechanical crusher. After crushing, the shells are sieved to remove impurities to obtain particles with a size of 100-180 mesh, 80-120 mesh and 40-80 mesh; the mass ratio of the three is 3:5:2.
[0034] 3. Preparation of shell powder: Put the crushed waste shells with a particle size of less than 5 mm into a ball mill for ball milling (ball milling at 60 rpm for 50-60 minutes). Pass the waste shell powder obtained after ball milling through a 0.6 mm round hole sieve to retain the shell powder with a particle size of less than 0.6 mm.
[0035] 4. Preparation of metakaolin powder:
[0036] The coal-bearing kaolinite is crushed step by step, ground and then pulverized to make the mass fraction of particles larger than 75 μm in the ground coal-bearing kaolinite powder less than 10%, then calcined at 800°C, kept warm and activated for 2 hours, quenched in water, dried and then ground, and passed through a 100-mesh sieve to obtain the desired metakaolin powder.
[0037] Step 2: Preparation of alkaline activator:
[0038] Put shell powder with a particle size not greater than 0.6 mm into a muffle furnace and calcine at 950°C for 2 hours. Stir and mix the shell powder once every hour. After calcination, cool it to room temperature and ball mill it for 1-2 minutes to obtain solid calcium oxide powder with a sieve residue rate similar to that of cement particles. Seal the calcium oxide powder for later use.
[0039] The lithium battery ternary precursor wastewater is filtered and impurities are removed, and sodium carbonate solution is added to precipitate lithium and other metal ions. After standing for 24 hours and completely precipitating, the precipitate is removed by centrifugation. The pH of the wastewater is adjusted to 8-9 using glacial acetic acid, and the wastewater is evaporated and concentrated by evaporation equipment to crystallize sodium sulfate and filter and separate it through filtering equipment.
[0040] Sodium sulfate and calcium oxide powder are mixed, and water is added to dissolve them, so that the mixed activator is completely dissolved in water and cooled to room temperature to form a uniform and clear mixed activator solution for use. The mixed mass ratio of sodium sulfate, calcium oxide powder and water is 330.39:62.81:236.93.
[0041] Step 3: Preparation of inorganic polymer repair material
[0042] Put the ceramic waste powder, shell fine aggregate, shell powder and metakaolin powder prepared in step 1 into a mixer, stir the dry material in the mixer for 1 to 2 minutes, then add the alkaline activator solution prepared in step 2 to the completely stirred dry material, and continue stirring for 3 minutes to allow the dry material to fully contact and react with the alkaline activator;
[0043] Alumina fibers are added to the mortar slurry at a uniform speed in batches, and stirring is continued for 10 minutes after all the alumina fibers are added to obtain an inorganic polymer repair material, wherein the mixing mass ratio of ceramic waste slag powder, shell fine aggregate, shell powder and metakaolin powder, alkali activator and alumina fibers is 180:900:450:360:393.2:19.4.
[0044] Embodiments 2 to 6
[0045] The methods of Examples 2 to 6 are the same as those of Example 1, except that the proportions of materials used in Examples 2 to 6 are different from those in Example 1. See Table 1 for details.
[0046] Table 1 - Amount of ingredients added in Examples 1 to 6
[0047]
[0048] The inorganic polymer repair materials prepared in Examples 1 to 6 were subjected to performance tests:
[0049] (1) The initial fluidity of the inorganic polymer repair materials prepared in Examples 1 to 6 was tested by the jumping table method to ensure that the working performance of the green and environmentally friendly inorganic mineral polymer repair materials prepared using solid waste met the requirements. The test results are shown in Figure 1 , it can be seen that the fluidity of each group is maintained above 200 mm, proving that the repair material is feasible in terms of fluidity.
[0050] (2) Pour the newly mixed inorganic polymer repair material prepared in Examples 1 to 6 into 40mm*40mm*160mm, dog bone tensile test molds 320mm*60mm*13mm and 100mm*100mm*300mm, and place in an environment (temperature 25°C, humidity 55%-65%) for curing for 24 hours. After 1 day, remove the sample from the test mold, wrap the test block with plastic wrap, and place it in a room temperature environment until the specified age. Within the specified age, the compressive strength, flexural strength, fold-to-compression ratio and tensile properties of the green and environmentally friendly inorganic polymer repair material test block are measured. The measurement results are shown in Figures 2 to 5 .
[0051] Figure 2 The 3d, 7d and 28d compressive strengths of the inorganic polymer repair material test blocks prepared in Examples 1 to 6 show that the 28d compressive strength of each group is above 40 MPa, which proves that the strength of the green and environmentally friendly repair material can be guaranteed and can reach the expected strength.
[0052] Figure 3 The 3d, 7d and 28d flexural strengths of the inorganic polymer repair material test blocks prepared in Examples 1 to 6 show that the 3d flexural strength of Example 4 (Group D) reaches the highest, and the 28d flexural strength also reaches about 7.5 MPa.
[0053] Figure 4 It is the ratio of compressive strength to flexural strength of each group and age of inorganic polymer repair material test blocks. The flexural-compression ratio can be used to evaluate the toughness of the material. Figure 4 It can be seen that with the increase of age, the fold-to-compression ratio gradually decreases, which also shows that the increase of 28d compressive strength is greater than the increase of flexural strength. In general, the fold-to-compression ratio of Example 4 (Group D) changes relatively stably.
[0054] Figure 5 The test results of the inorganic polymer repair material test block prepared in Example 4 (Group D) under tensile test show that the tensile strain of the test block under this ratio reaches 3%, and the tensile strength reaches 4.5 MPa.
[0055] Example 7
[0056] During the curing stage after the repair material is poured, the internal temperature may rise due to hydration heat. However, due to the poor thermal conductivity of the structure itself, a large amount of heat accumulates inside the component, making the temperature high inside and low outside, and the temperature difference is large, forming temperature stress. When the generated temperature stress (usually tensile stress) exceeds the tensile strength at that time, surface cracks are likely to form.
[0057] In view of the above problems, the present invention provides an application method of an inorganic polymer repair material, wherein the application method is:
[0058] Before construction, software simulation calculations are used to determine the position where the component's internal temperature rises the highest due to hydration heat generated during the component's hardening process. During construction, the cold end of the Stirling refrigerator is placed near it, and the cold end of the Stirling refrigerator is cast inside the part to be repaired using an inorganic polymer repair material. At the same time, the temperature change inside the component is monitored through a temperature sensor installed at the front end. When the cast part begins to harden, the temperature sensor detects that the temperature difference between its internal temperature and the surface temperature exceeds the threshold, and then turns on the Stirling refrigerator to cool the inside of the cast part, so that the temperature difference between the inside and outside of the building is within the specified range during the entire curing process. When the cast part is completely hardened, the Stirling refrigerator is removed, and the cavity formed by the removal of the Stirling refrigerator is filled with repair material, and finally the surface is covered with the repair material.
[0059] The green and environmentally friendly repair material prepared by the present invention does not use cement as a cementitious material at all, thus avoiding the pollution of the cement production process and the impact of industrial dust emissions on the environment. In addition, the waste ceramsite, shells, recycled coal-based kaolin, lithium battery ternary precursor wastewater, and alumina fiber used to prepare inorganic mineral polymer materials consume a large amount of waste ceramsite, accumulated shells and coal-based kaolin waste, so that solid waste is effectively utilized while reducing resource waste. More importantly, the use of treated wastewater from lithium battery factories and calcined shells as alkaline activators reduces their pollution to the environment, while avoiding the negative impact of traditional alkaline activators such as sodium hydroxide and water glass on the surrounding environment, thereby reducing the cost of use.
[0060] The above are only preferred embodiments of the present invention, and the protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, some improvements and modifications without departing from the principle of the present invention should be regarded as the protection scope of the present invention.
Claims
1. A method for preparing an inorganic polymer repair material, characterized in that: The following steps are involved: Mix and stir the ceramic waste powder, shell fine aggregate, shell powder and metakaolin powder, then add the alkali activator solution to the completely stirred dry material, and continue stirring to make the dry material and the alkali activator fully contact and react; Alumina fibers are added into the mortar slurry at a uniform speed in batches, and stirring is continued after all the alumina fibers are added to obtain an inorganic polymer repair material.
2. The method for preparing an inorganic polymer repair material according to claim 1, characterized in that: The mixing mass ratio of the ceramic waste powder, shell fine aggregate, shell powder and metakaolin powder, alkali activator and alumina fiber is (180-450):900:(180-450):(180-360):393.2:19.
4.
3. The method for preparing an inorganic polymer repair material according to claim 1, characterized in that: The preparation method of the ceramic waste powder is: The ceramic waste slag is cleaned and dried to constant weight, and then sieved after being cooled to room temperature. The sieved ceramic waste slag is ball-milled to obtain ceramic waste slag powder, wherein the particle size of the ceramic waste slag powder is not greater than 10 μm.
4. The method for preparing an inorganic polymer repair material according to claim 1, characterized in that: The shell fine aggregate is prepared by washing the discarded shells with acetic acid to remove the organic matter remaining on the surface thereof, then washing, drying and crushing, and sieving and removing impurities after crushing to obtain particles with a size of 100-180 mesh, particles with a size of 80-120 mesh, and particles with a size of 40-80 mesh; the mass ratio of the three is 3:5:2; The shell powder is obtained by ball-milling and sieving crushed discarded shells, and the particle size of the shell powder is no more than 0.6 mm.
5. The method for preparing an inorganic polymer repair material according to claim 1, characterized in that: The preparation method of the base activator is: The shell powder with a particle size not greater than 0.6 mm is calcined at high temperature, cooled to room temperature, and ball-milled to obtain calcium oxide powder; The lithium battery ternary precursor wastewater is filtered and impurities are removed, sodium carbonate solution is added and then centrifuged to remove precipitation, the pH is adjusted to 8-9, the wastewater is evaporated and concentrated, sodium sulfate crystals are precipitated and filtered and separated; sodium sulfate and calcium oxide powder are mixed, water is added to dissolve, and cooled to room temperature to obtain an alkaline activator solution.
6. The method for preparing the inorganic polymer repair material according to claim 5, characterized in that: The high temperature calcination temperature is 950°C and the calcination time is 2 hours; The mixing mass ratio of the sodium sulfate, calcium oxide powder and water is 330.39:62.81:236.
93.
7. The method for preparing an inorganic polymer repair material according to claim 1, characterized in that: The preparation method of the metakaolin powder is: The coal-bearing kaolinite is crushed step by step, ground and then pulverized to make the mass fraction of particles larger than 75 μm in the pulverized coal-bearing kaolinite powder less than 10%, then calcined at high temperature, kept warm and activated for a period of time, quenched and cooled with water, dried and then ground and sieved to obtain the desired metakaolin powder.
8. The method for preparing an inorganic polymer repair material according to claim 7, characterized in that: The calcination temperature is 800° C. and the heat preservation activation time is 2 hours.
9. A method for applying the inorganic polymer repair material prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The application method is: The cold end of the Stirling refrigerator is placed in the part to be repaired, and the inorganic polymer repair material is poured on the part to be repaired. When the poured part begins to harden and the temperature difference between its internal temperature and the surface temperature exceeds a threshold, the Stirling refrigerator is turned on to cool the inside of the poured part. When the poured part is completely hardened, the Stirling refrigerator is removed, and the cavity formed by the removal of the Stirling refrigerator is filled with the repair material, and finally the surface is covered with the repair material.
Citation Information
Patent Citations
Geopolymer prepared from Liling ceramic wastes as well as preparation method and application thereof
CN104193203A
Curing device and method for internal cooling and humidification of mass concrete
CN109372263A
Method of preparing environment-friendly inorganic ore polymer mortar by using solid wastes
CN109503042A